Las buenas prácticas manufactureras "BPM" y su relación en el proceso productivo de la Empresa Alcopesa S.A. - Pruna Tapia, Carlos Xavier (2017)
The purpose of this project is to analyze the non-observance of good manufacturing practices in the production processes of the company ALCOPESA SA, the company when producing whiskey, must take into account several aspects for the production of liqueurs, such as, quality of the material premium and inputs, capacity of the machinery, trained personnel, standards of salibrity and production of that type of product. For which the relationship between good manufacturing practice and the productive process of the industry must be determined, this was achieved through the analysis of the procedures of the companies engaged in the elaboration of alcoholic beverages, for which the observation of the productive process of the company ALCOPESA SA The study has a scientific extract about the characteristics of good manufacturing practices, the safety of products for human consumption, the types of food risks, the regulations of the National Agency for Regulation and Health Surveillance Control (ARCSA). The research has a quantitative approach, with a type of descriptive research, which through the deductive, synthetic, analytical method can be deduced from a general context of the practice of the BPM in the company, the survey as a technique for collecting information provided the data to the workers of the company. An analysis and interpretation of the inquiry made as a result that the user recognizes that the application of the BPM is necessary for an efficient task. The training of the personnel on the use of the equipment of empowerment and its necessity within the process of elaboration, establishing policies that impel in the workers to apply the norms of handling of the hygiene and the health of the personnel. It is recommended to determine a preventive maintenance program, the same one that has a small action of actions taken to determine the damages in the machinery and equipment of the company ALCOPESA S.A.